Direct-fed microbials for receiving cattle II: Effects of ProTernative stress formula fed in a dry suspension on growth, feed intake, and health of receiving beef heifers - A.V. Siverson; M.E. Corrigan; James J. Higgins; Dale A. Blasi; Brandon E. Oleen (Kansas Agricultural Experiment Station Research Reports, 2012)
Enhanced preconditioning and nutritional management strategies are needed industrywide as a means of controlling stress and related health problems for freshly arrived stocker calves. Direct-fed microbials are feed additives that stimulate natural, nonpathogenic gut flora in an attempt to stimulate competition against potentially pathogenic gut flora. Previous research involving direct-fed microbials offered in a liquid suspension to lightweight stocker calves produced no effects on growth or health performance. Therefore, the objective of our study was to evaluate the effects of a directfed microbial offered as a dry suspension on feed intake, average daily gain, and morbidity of highly stressed beef heifers.
Keywords: Cattlemen& #x27; s Day; 2012; Kansas Agricultural Experiment Station contribution; no. 12-231-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1065; Beef Cattle Research; 2012 is known as Cattlemen& #x27; s Day; Beef; Microbials; ProTernative stress formula; Growth; Feed intake; Health